2013
DOI: 10.2298/gensr1301153a
|View full text |Cite
|
Sign up to set email alerts
|

Effective selection criteria for screening drought tolerant recombinant inbred lines of sunflower

Abstract: In this study, seventy two sunflower recombinant inbred lines were tested for their yielding ability under both water-stressed and well-watered states. The inbred lines were evaluated in a rectangular 8´9 lattice design with two replications in both well-watered and water-stressed conditions, separately. Eight drought tolerance indices including stability tolerance index (STI), mean productivity (MP), geometric mean productivity (GMP), harmonic mean (HM), stress susceptibility index (SSI), tolerance inde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
5
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 23 publications
7
5
1
Order By: Relevance
“…Positive correlation between seed cotton yield in DI and FI shows that high yielding in the DI was also high yielding in FI environment. These results agree with those reported by Ramirez Vallejo and Kelly (1998) and Teran and Singh (2002) in common bean, Abdi et al (2013) in sunflower, Khokhar et al (2012) in barley. However, there have been contradictory reports in the literature, Gholipouri et al (2009) and Anwar et al (2011) reported that, the yield under irrigated conditions has a very weak association with stress conditions, therefore, indirect selection for stresses environment based on the performance of irrigated conditions would not be effective in wheat.…”
Section: Resultssupporting
confidence: 92%
“…Positive correlation between seed cotton yield in DI and FI shows that high yielding in the DI was also high yielding in FI environment. These results agree with those reported by Ramirez Vallejo and Kelly (1998) and Teran and Singh (2002) in common bean, Abdi et al (2013) in sunflower, Khokhar et al (2012) in barley. However, there have been contradictory reports in the literature, Gholipouri et al (2009) and Anwar et al (2011) reported that, the yield under irrigated conditions has a very weak association with stress conditions, therefore, indirect selection for stresses environment based on the performance of irrigated conditions would not be effective in wheat.…”
Section: Resultssupporting
confidence: 92%
“…Genotypes 8, 9 and 7 with high SSI values (1.97, 1.45 and 1.45, respectively) can be considered drought susceptible. Similar results were found in those of Abdi et al (2013) and Raman et al (2012).…”
Section: Mean Performance Of Genotypes Based On the Tolerance Indicessupporting
confidence: 89%
“…The variation in Yp and Ys suggested the occurrence of important resources for getting drought tolerant genotypes under this study. The results are similar to those of Abdi et al (2013). STI ranged from 0.22 to 1.39; the higher values of up to 1 indicate high stress tolerance.…”
Section: Mean Performance Of Genotypes Based On the Tolerance Indicessupporting
confidence: 82%
“…These STIs are stress susceptibility index (SSI) [114], geometric mean productivity (GMP) [115], mean productivity (MP) [116], stress tolerance (TOL) [117] and STI [118] that can be useful for documentation of stress tolerance crops cultivars with high-yield ability. Among STIs, genotypes with higher values for each of MP [47,119], GMP [118,120], yield index (YI) [121,122], yield stability index (YSI) [119,123] and relative performance (RP%) [23,33] suggest higher stress tolerance compared to lower tolerance for lower values of these indices. Whereas, the lower value of SSI of a crop cultivar indicates that the cultivar is tolerant to stress, while a higher SSI value indicates relatively greater sensitivity to a given stress [110,[124][125][126].…”
Section: Stress Tolerance Indices Could Be Used Effectively For the Smentioning
confidence: 99%